Activation of Aryl Carboxylic Acids by Diboron Reagents towards Nickel‐Catalyzed Direct Decarbonylative Borylation. (7th August 2021) - Deng, Xi; Guo, Jiandong; Zhang, Xiaofeng; Wang, Xiaotai; Su, Weiping
Abstract: The Ni‐catalyzed decarbonylative borylation of (hetero)aryl carboxylic acids with B2 cat2 has been achieved without recourse to any additives. This Ni‐catalyzed method exhibits a broad substrate scope covering poorly reactive non‐ ortho ‐substituted (hetero)aryl carboxylic acids, and tolerates diverse functional groups including some of the groups active to Ni 0 catalysts. The key to achieve this decarbonylative borylation reaction is the choice of B2 cat2 as a coupling partner that not only acts as a borylating reagent, but also chemoselectively activates aryl carboxylic acids towards oxidative addition of their C(acyl)−O bond to Ni 0 catalyst via the formation of acyloxyboron compounds. A combination of experimental and computational studies reveals a detailed plausible mechanism for this reaction system, which involves a hitherto unknown concerted decarbonylation and reductive elimination step that generates the aryl boronic ester product. This mode of boron‐promoted carboxylic acid activation is also applicable to other types of reactions. Abstract : A Ni‐catalyzed direct decarbonylative borylation of aryl carboxylic acids with B2 cat2 has been established. B2 cat2 serves as a borylating agent, but also activates the carboxylic acid substrate towards decarbonylative coupling, playing a dual role in this reaction. A combination of experimental and computational studies reveals that the reaction proceeds through a hitherto unknown concerted decarbonylation and reductive elimination step.